1996
DOI: 10.1145/250707.239108
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of object behavior using context relations

Abstract: A collection of design patterns was described by Gamma, Helm, Johnson, and Vlissides in 1994. Recognizing that designs change, each pattern ensures that a certain system aspect can vary over time such as the operations that can be applied to an object or the algorithm of a method. The patterns are described by constructs such as the inheritance and reference relations, attempting to emulate more dynamic relationships. As a result, the design patterns demonstrate how awkward it is to program natural concepts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Research on the use of visitors in this capacity is sparse. Seiter, Palsberg, and Leiberherr suggest similar uses to illustrate that the visitor pattern is difficult to use for analyses that require a lot of context [19]. While we agree with their assessment in general, we believe that visitor-based solutions in existing programming languages are sufficient for many analysis problems that arise in software-engineering environments.…”
Section: Related Workmentioning
confidence: 58%
See 1 more Smart Citation
“…Research on the use of visitors in this capacity is sparse. Seiter, Palsberg, and Leiberherr suggest similar uses to illustrate that the visitor pattern is difficult to use for analyses that require a lot of context [19]. While we agree with their assessment in general, we believe that visitor-based solutions in existing programming languages are sufficient for many analysis problems that arise in software-engineering environments.…”
Section: Related Workmentioning
confidence: 58%
“…Despite our success in analyzing formal specifications, we found that to implement more sophisticated program analyses requires the management of a significant amount of analysis context by the visitor. Unfortunately, visitors that must manage a large amount of context can be very difficult to design and to understand [19].…”
Section: Amalia Tool Suitementioning
confidence: 99%
“…The pattern fixes the traversal order of the visited structures; a typical analysis needs to consider information located in multiple locations instead of cleanly hierarchical structures. This kind of analysis of multiple fragments is awkward with the visitor pattern [10]. Refinements for applying the visitor pattern include a system of multiple curried visitors, among other things [11].…”
Section: Bcelmentioning
confidence: 99%
“…Other approaches are Mixins [5], composition filters [1], aspect-oriented programming [7,14] and [6]. One of the main ingredients for feature-oriented programming, adapting to a context, can also be found in [21]. These approaches do however not cover graphic design methods.…”
Section: Conclusion and Related Workmentioning
confidence: 99%